Bacterial internalization mediated by beta 1 chain integrins is determined by ligand affinity and receptor density. - Tran Van Nhieu, G (1993)
Binding of bacteria to beta 1 chain integrin receptors results in either bacterial adherence or uptake by cultured cells (Isberg, 1991). In this report we show that Staphylococcus aureus coated with high affinity ligands for the beta 1 chain integrin family can be internalized efficiently, whereas bacteria coated with low affinity ligands are poorly internalized. Overproduction of the alpha 5 beta 1 integrin increased the efficiency of bacterial internalization, indicating that the uptake efficiency is directly related to the level of expression of the receptor. By using latex beads or S. aureus coated with mAbs directed against the alpha 5 beta 1 integrin, a roughly semi-logarithmic correlation was observed between the affinity of the receptor-ligand interaction and the rate of bacterial internalization. Evidence is presented that high affinity binding of the bacterium allows the microorganism to compete efficiently with receptor-ligand interactions at the basolateral surface of the cell.